2006
DOI: 10.1016/j.cardiores.2005.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Autologous myoblast transplantation after myocardial infarction increases the inducibility of ventricular arrhythmias

Abstract: In an infarcted rat model, myoblast transplantation but not bone marrow mononuclear cells or myocardial injection per se induces electrical ventricular instability. Because ventricular arrhythmias are life-threatening disorders, we suggest that such preclinical evaluation should be conducted for any new source of cells to be injected into the myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 29 publications
5
93
0
Order By: Relevance
“…In a rat model of myocardial infarction, Fernandes et al 12 used programmed electrical stimulation and showed an increased inducibility of ventricular arrhythmias in myoblast-injected hearts compared with controls. Of note, however, an implantable telemetry system failed to document a difference in the number of arrhythmic episodes between myoblast-injected rats and those receiving control medium.…”
Section: Skeletal Myoblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a rat model of myocardial infarction, Fernandes et al 12 used programmed electrical stimulation and showed an increased inducibility of ventricular arrhythmias in myoblast-injected hearts compared with controls. Of note, however, an implantable telemetry system failed to document a difference in the number of arrhythmic episodes between myoblast-injected rats and those receiving control medium.…”
Section: Skeletal Myoblastsmentioning
confidence: 99%
“…5 However, such a hypertrophy has not been found consistently. 12 Overall, these coculture experiments have been helpful in deciphering the potential mechanisms underlying arrhythmias, but one of their limitations is the use of a 2-dimensional monolayer. The incidence of arrhythmias might actually be lower in the 3-dimensional heart because of the greater number of pathways available for propagation of electrical influxes around the localized barriers formed by engrafted cells interspersed around host cardiomyocytes.…”
Section: Skeletal Myoblastsmentioning
confidence: 99%
“…Preclinical animal studies have demonstrated the ability for skeletal myoblasts to engraft, form myotubules and enhance cardiac function after transplantation into infarcted myocardium [15]. Unfortunately, it appears that the grafts do not couple electrically with adjacent cardiomyocytes [16] and these islands of transplanted cells with different electrophysiological properties, may serve as an arrhythmogenic substrate [17].…”
Section: Adipose and Skeletal Muscle Derived Stem Cellsmentioning
confidence: 99%
“…The first relevant large-scale randomized clinical trial looking into this was the MAGIC (Myoblast Autologous Grafting in Ischemic Cardiomyopathy) trial which suggested that engraftment of unmodified skeletal myoblasts may generate arrhythmias [13,14]. However, data from more recent large trials show that ventricular arrhythmic events did not differ after intramyocardial injection of skeletal myoblasts or placebo [15].…”
Section: Arrhythmia As a Side Effect Of Cell Transplantationmentioning
confidence: 99%